A conceptual IT governance and green IT model to support large organisations - Hardin-Ramanan, S.; Chang, Vanessa; Issa, Tomayess (IADIS Press, 2012)
The role of Information Technology (IT) as a powerful business enabler has now taken a ‘green’ turn for the achievement of enterprise sustainability goals. Yet, taking appropriate IT decisions for added business value and especially to meet the ‘green’ or sustainability expectations of society remains a major challenge. For many organisations, effective IT Governance including Green IT seems to be the key to this problem, especially for large organisations reputed for superior IT expertise and resources. However, although some studies have investigated IT Governance and Green IT, none have been framed around an in-depth investigation of both. Numerous calls for further investigation on IT Governance and Green IT have also been made in the literature. Addressing these needs, IT Governance and Green IT decision types, accountabilities and mechanisms from the literature were explored to develop a conceptual IT Governance and Green IT model (ITGM). Driven by the Mauritian government’s vision of Sustainable Mauritius, future study shall refine the ITGM in the context of large Mauritian organisations from the four pillars of the Mauritian economy to guide them in optimising the business-enhancing and ‘greening’ potential of IT.